New Schiff base chromophores composed of salicylaldehyde and naphthalimide derivatives for ion sensor applications. Issue 28 (8th July 2019) - Yan, Han; Zhong, Kailiang; Lu, Yun
Abstract : New Schiff base chromophores with salicylaldehyde and naphthalimide structures were synthesized and characterized using IR, 1 H NMR, 13 C NMR and HRMS. Abstract : New Schiff base chromophores with salicylaldehyde and naphthalimide structures were synthesized and characterized using IR, 1 H NMR, 13 C NMR and HRMS. They all exhibited obvious solid-state fluorescence features because of their inherent twisted structures, and some of them showed high selectivity and sensitivity for Mg 2+ detection due to the dual contributions of excited-state intramolecular proton transfer and an aggregation-induced emission effect. For these new Schiff base chromophores, it was found that adjusting the substituents with different electronic properties on the salicylaldehyde unit could fine-tune their range of emission wavelengths and photophysical properties. Also, changing the chain length based on the –N–NC– structure could influence their response to metal ions. The research results provide valuable information and ideas on the molecular design of novel fluorescence materials and related specific applications.